BAKTERI Bacillus coagulans SEBAGAI FEED PROBIOTIC UNTUK MENINGKATKAN PERFORMA UDANG JERBUNG Fenneropenaeus merguensis (de Man, 1888) - Supono, Supono; Taqiyatin, Hani; Harpeni, Esti (University of Prof. Dr. Hazairin, SH, 2020)
Banana shrimp (Fenneropenaeus merguensis) is an alternative species of local Indonesian shrimp that has the opportunity to be commercially cultivated. One important factor that influences shrimp growth is the feed. Improving the quality of shrimp feed can be done by adding probiotics, one of which is by using Bacillus coagulans. The purpose of this research was to study the effect of B. coagulans bacterium on feed on the growth, feed conversion ratio, and survival rate of Jerbung shrimp. This research was carried out for 35 days. The study design used was a completely randomized design consisting of 4 treatments and 3 replications. The treatment was in the form of feed mixed with B. coagulans with a dose of 0 ml/kg of feed (control), 10ml×106CFU/kg of feed, 20ml×106CFU/kg of feed, and 30ml×106CFU/kg of feed. The results showed that the administration of B. coagulans mixed in the feed significantly affected the growth of weight, length, daily growth rate, feed conversion ratio, and protein efficiency ratio, not significantly different from the survival rate of the jerbung shrimp. The best treatment occurred in the treatment of B. coagulans 10ml×106 CFU/kg of feed.